Two Serbias and their Vision of Europe: A Discursive Perspective (KULT_online, 2016)
In her recent book Divided We Stand: Discourses on Identity in 'First' and 'Other' Serbia Ana Russell-Omaljev offers a study of the political discourses and divisions within contemporary Serbian society while referencing the discursive construction of Europe and Serbian identity. Employing discourse analysis and the concepts of 'Self' and 'Other' from critical constructivist theory, the book's aim is to contribute to an understanding of 'othering' within Serbia and in relation to Europe. Encompassing a long time span, from 1987 to 2012, the book provides an insight into the dynamics of politics and identity in Serbian society.